Perhitungan Biaya Pemasukan Dalam Menetapkan Harga Jual Dan Jasa Pada PT Trimitra Solusindo - Hendriyati Haryani; Mutiara Angela; Nurmaida Azizah Al Wahni (IJAcc, 2022)
This research aims to analyze the calculation of the order budget in setting the selling price at PT Trimitra Solusindo. Analysis of determining the cost of goods sold with the Full Costing method approach. The cost of goods ordered through the Full Costing method at PT Trimitra Solusindo in 2014 was Rp. 91.910.000,- while the cost of goods sold was Rp. 175.000.000,-. In 2015 the cost of production through the Full Costing method of PT Trimitra Solusindo experienced an increase to Rp. 142.805.000,- while the cost of goods sold was Rp. 273.000.000,-. The increase in the cost of production and the cost of goods sold was due to the increase in the number of Rosban production at PT Trimitra Solusindo, so that the entire existing budget also experienced an increase. The selling price of rosban which must be inaugurated by PT Trimitra Solusindo in order to obtain a profit in accordance with its target in 2014 is Rp. 3.500.000 per unit, while in 2015 the selling price of rosban which must be inaugurated by PT Trimitra Solusindo in order to earn a profit is in accordance with its target, namely: IDR 4,200,000 per unit.